2023
DOI: 10.7717/peerj.14799
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin specific peptidases and prostate cancer

Abstract: Protein ubiquitination is an important post-translational modification mechanism, which regulates protein stability and activity. The ubiquitination of proteins can be reversed by deubiquitinating enzymes (DUBs). Ubiquitin-specific proteases (USPs), the largest DUB subfamily, can regulate cellular functions by removing ubiquitin(s) from the target proteins. Prostate cancer (PCa) is the second leading type of cancer and the most common cause of cancer-related deaths in men worldwide. Numerous studies have demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 128 publications
0
8
0
Order By: Relevance
“…In prokaryotes, ClpP and Lon are the major proteasomes that participate in the proximal ATP-dependent steps of substrate degradation [ 10 ]. UPS participates in intracellular protein proteasome-dependent degradation, cell metabolism, cell cycle progression, chromosome separation, kinase activation, apoptosis, DNA repair, and so on [ 11 , 12 , 13 ]. Ubiquitination modification is a primary mode of intracellular protein degradation in eukaryotes mediated by ubiquitin; it is initiated by enzyme E1 (ubiquitin-activating enzyme), which generates thioester bonds between its Cys residue and the ubiquitin C terminus using ATP-dependent hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In prokaryotes, ClpP and Lon are the major proteasomes that participate in the proximal ATP-dependent steps of substrate degradation [ 10 ]. UPS participates in intracellular protein proteasome-dependent degradation, cell metabolism, cell cycle progression, chromosome separation, kinase activation, apoptosis, DNA repair, and so on [ 11 , 12 , 13 ]. Ubiquitination modification is a primary mode of intracellular protein degradation in eukaryotes mediated by ubiquitin; it is initiated by enzyme E1 (ubiquitin-activating enzyme), which generates thioester bonds between its Cys residue and the ubiquitin C terminus using ATP-dependent hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that changes in the ubiquitin system may lead to the occurrence of human diseases (Mooney & Sahingur, 2021). Ubiquitinated degradation of genes is a widespread posttranslational modification that plays an important biological regulatory role in cells (Guo et al., 2023; Qin et al., 2022). Studies had shown that USP47 could directly stabilize BACH1 to enhance NSCLC tumor growth by deubiquitination (Peng et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination is involved in the regulation of various protein functions including cell proliferation, cell cycle, DNA damage repair and transmembrane transportation by the regulation of ubiquitin and deubiquitination enzymes (DUBs), among which ubiquitin speci c peptidases (USPs) play the most signi cant role [34]. Each ubiquitin molecule is contained by seven lysine (K) residues (K6, K11, K27, K29, K33, K48, and K63), as well be assembled into eight types of ubiquitin chain linkages through covalently conjugating the C-terminal glycine of a second ubiquitin molecule with one of the seven lysine residues or the aminoterminal methionine (Met1) on the rst ubiquitin moiety.…”
Section: Discussionmentioning
confidence: 99%